Plan de estrategias en comunicación asertiva para mejorar la relación entre el clima organizacional y el desempeño laboral en la IE Maynas Iquitos 2022 - Núñez Dávila, Lourdes Amelia (2024)
The thesis Plan of strategies in assertive communication to improve the relationship between organizational climate and work performance in IE. Maynas Iquitos 2022, explanatory research, used a quasi-experimental design. The objective: To explain the effects produced by the strategy plan in assertive communication to improve the relationship between the organizational climate and work performance in the Maynas Educational Institution. Iquitos. 2022. Sample: 30 members. Maynas. Results: It was determined that before the application of the strategy plan, assertive communication is not related to the organizational climate (p>0.005), the same happens with work performance (p>0.005). After the implementation of the plan, it was determined that assertive communication significantly improves work involvement (p=0.000), communication (p=0.000), working conditions (p=0.001); Likewise, the application of the assertive communication plan improves the quality of work (p=0.004), work discipline (p=0.049), teamwork (p=0.005). In conclusion, assertive communication improves the organizational climate and the work performance of teachers at Maynas educational institution. Iquitos. 2022.